Cognitive dysfunction after ischemic stroke - Ozdogru, Derya; Erdem, Miray (The European Research Journal, 2025)
Objectives: One of the most important and common consequences of ischemic stroke is the cognitive impairment observed after stroke. This study aimed to investigate the role of strategic stroke among post-stroke cognitive impairment using the Montreal Cognitive Assessment Scale (MOCA). Methods: This study was planned as a prospective cross-sectional study. Patients admitted between 3 and 12 months after stroke were included in the study. Patients who had a stroke at least 3 months ago, who had not been admitted for a year after the stroke, and who gave consent to participate in the study were considered as inclusion criteria. Results: This study included 45 (44.1%) females and 57 (55.9%) males. When evaluated in terms of comorbidity, the frequency of hyperlipidemia was found to be significantly higher in the cognitively impaired group (46.5% vs. 25.4%, P=0.027). Thyroid stimulating hormone (TSH) levels were found to be lower in the Cognitive Impairment Group (0.93 μIU/mL vs. 1.03 μIU/mL, P=0.021). Considering the finding rates and significance level of lesion sites between the groups, the strategic infarction rate was found to be significantly higher in the cognitively impaired group (62.8% vs. 33.9%, P=0.004). In cognitive tests, the cognitive impairment group showed significantly lower performance in all areas (P